Basketball in physical education of non sport universities - Zaschuk S.G; Ivchatova T.V (Kharkov National Pedagogical University, 2010)
A health of students of unathletic institutes of higher level is studied. It is rotined that over modernization of the system of physical education brought to considerable reduction of audience employments on a physical culture. Connection is considered between the low level of health of student young people and reduction of audience employments on physical education. Insufficient motivation is marked to independent employments by physical exercises, decline of motive activity of students. Efficiency of application of basket-ball is grounded in the process of physical education of students.